Perbandingan Epistemologi Al-Farabi dan Immanuel Kant Tentang Rasionalitas - Binti Khalimatuzzahro; Irham Multazam (IDRIS Darulfunun Institute, 2026)
Rationality is a central theme uniting Islamic and Western philosophical traditions, although the two proceed from different metaphysical frameworks. This paper aims to comparatively examine the epistemology of Al-Farabi (d. 950 CE), known as the